(untitled) (ModaPalavra e-periódico, 2015)
The consumer society has undergone transformations and especially in fashion, innovation and market differentiation become decisive factors for organizations. The design can bea great ally of the companies in this context. This article aims to evaluate the perceptions of experts on the strategic positioning through design and it was developed a qualitative approach with professionals working in the areas of design, marketing and fashion. The result demonstrated the strategic importance of integrated design to marketing in management levels, as a means of achieving competitive advantages and important aid in developing strategies of segmentation and positioning. Design can promote many benefits to businesses and especially favors the understanding of needs, desires and future demands of the fashion market, which may be essential in the relationship between companies and customers, developed by marketing.